Home » Simplify (frac{sqrt{12} – sqrt{3}}{sqrt{12} + sqrt{3}})

Simplify (frac{sqrt{12} – sqrt{3}}{sqrt{12} + sqrt{3}})

Simplify (frac{sqrt{12} – sqrt{3}}{sqrt{12} + sqrt{3}})

  • A.
    (frac{1}{3})
  • B.
    9
  • C.
    16cm
  • D.
    3
Correct Answer: Option A
Explanation

(frac{sqrt{12} – sqrt{3}}{sqrt{12} + sqrt{3}})

(sqrt{12} = sqrt{4 times 3} = 2sqrt{3})

(therefore frac{sqrt{12} – sqrt{3}}{sqrt{12} + sqrt{3}} = frac{2sqrt{3} – sqrt{3}}{2sqrt{3} + sqrt{3}})

= (frac{sqrt{3}}{3sqrt{3}})

= (frac{1}{3})

Related:  if (frac{4m+3n}{4m-3n}=frac{5}{2}), find the ratio m:n